Prevalence, risk factors and impact of posterior staphyloma diagnosed from wide‐field optical coherence tomography in Singapore adults with high myopia - Zheng, Feihui; Wong, Chee‐Wai; Sabanayagam, Charumathi; Cheung, Yin‐Bun; Matsumura, Saiko; Chua, Jacqueline; Man, Ryan Eyn Kidd; Ohno‐Matsui, Kyoko; Wong, Tien‐Yin; Cheng, Ching‐Yu; Tai, E. Shyong; Lamoureux, Ecosse Luc Edouard Denis; et al. (Acta ophthalmologica (Oxford, England), 2021)
Purpose To investigate the prevalence and risk factors of posterior staphyloma using wide‐field optical coherence tomography (WF‐OCT) in adults with high myopia in Singapore. Design Population‐based cross‐sectional study. Methods Adults with spherical equivalent (SE) ≤ −5D in either eye at the first visit of Singapore Epidemiology of Eye Diseases study and Singapore Prospective Study Program study were recruited. Posterior staphyloma was diagnosed using WF‐OCT (PLEX®Elite9000, Carl Zeiss Meditec). Myopic macular degeneration (MMD), myopic traction maculopathy (MTM) and vision‐related quality of life (VRQoL) were assessed using fundus photographs, DRI‐Triton OCT (Topcon) and the Impact of Vision Impairment (IVI) questionnaire, respectively. Factors associated with posterior staphyloma were identified with multilevel, multivariable logistic regression. Impact of posterior staphyloma on MMD, MTM and visual function was analysed with multilevel, multivariable logistic regression and linear mixed model, respectively. Results Among the 225 eyes [mean SE = −6.5 ± 2.2 D, mean axial length (AL) = 26.2 ± 1.5 mm] of 117 participants (mean age = 60.3 ± 7.1 years), posterior staphyloma was detected in 47 (20.9%) eyes of 38 (32.5%) participants. Older age [odds ratio (OR), 1.18; 95% confidence interval (CI), 1.10–1.26], more myopic SE (0.63; 0.51–0.77) and increased AL (2.51; 1.69–3.73) were associated with higher prevalence of posterior staphyloma (all p < 0.001). Adults with posterior staphyloma had higher odds of MMD (2.67; 1.23–5.82; p = 0.013), MTM (3.79; 1.13–12.68; p = 0.031) and worse IVI Reading (β = −1.44; −2.31 to 0.58; p = 0.001) scores. Conclusions About one in three adults with high myopia had posterior staphyloma, which was associated with increased odds of having myopic maculopathy and a detrimental impact on VRQoL.